Transformation Academic Integrity : Literature Review Shift Behavior Gen Z Learning in the Generative AI Era - Imam Al Fazari; M Firdaus; Dahlia Bonang (International journal of technology and education research, 2026)
Normalization use Generative Artificial Intelligence (Gen-AI) has trigger disruption big in ecosystem education high , especially to pattern behavior Study student Generation Z. Research This aim For dissect transformation behavior Gen Z learning and reconstructing meaning integrity academics in the era of intelligence artificial . Using method studies library research with​​ approach qualitative descriptive research​ This synthesize literature latest and empirical data about Students' digital habits . Research results show existence fundamental shift in pattern behavior Study from method exploratory - manual towards method instant-instructive based prompting . Data shows that ChatGPT dominates usage (57.9%) with activity main look for reference assignment (86%). However , it was found gap ethical where 50.5% of respondents sometimes do copying answer in a way directly , which triggers phenomenon lethargy cognitive and digital dependency (56.1%). Research This conclude that integrity academics in the AI era need defined repeat No just as compliance administrative to tool detection plagiarism , but rather as moral commitment to the dialectical process intellectual and ethical validation . The implications of study This demand existence innovation design more learning​ adaptive to Gen Z's digital characteristics without sacrifice depth think critical .